Ensaios farmacológicos e toxicológicos pré-clínicos com Zizyphus joazeiro Mart - Estevam, Ethiene Castellucci (2012)
Zizyphus joazeiro Mart. is a plant of the Rhamnaceae family, popularly known as "juazeiro" or "juá", and its leaves and bark are traditionally used by the population of northeastern Brazil as a febrifuge, antiinflammatory, in the treatment of stomach problems, skin diseases and as a hair and teeth cleaning. The wide use of this plant species for medicinal purposes by the population justifies pharmacologycal and toxicological studies to ensure the safety and efficacy of its use. In this sense, a study of its healing activity in experimentally induced excisional skin wounds and antiinflammatory action through the models of paw edema and peritonitis induced carrageenan and a toxicological preclinical acute and subchronic, lasting 21 days of the ethanol extract of stem bark of Z joazeiro after dermal application were proposed. In animal models assessed, Z joazeiro demonstrated positive activity on wound healing, improving their clinical signs. At doses of 35 and 175 mg/kg administered for 7 days, the paw edema and leukocyte migration into the peritoneal cavity after stimulation promoted by carrageenan were reduced. The results obtained through toxicological tests show that the extract is slightly irritating to skin at a dose of 1000 mg/kg, and is capable of inducing changes in water and food intake. When applied for 21 days at doses of 4, 8 and 16mg/kg, the plant caused flaking of the skin application site, changed the water and, food intake and body weight in males and females treated with the higher dose. Changes were found in creatinine levels in both sexes, triglycerides and platelet counts in males. Despite being considered a species with dermatocosmetic properties and low dermal toxicity, its continued use by the population should be done cautiously.